Сomputer simulation of positive streamer dynamics in uniform and non-uniform electric fields in air - Manuilenko, O.V. (Вопросы атомной науки и техники, 2013)
The results of numerical simulations of the propagation of a positive streamer in air in the uniform and strongly non - uniform electric fields are presented. It is shown that the dynamics of the streamer propagation in air retains the main features characteristic of a negative streamer in nitrogen. It is shown that the velocity of the streamer in a non - uniform electric field is higher than its velocity in an uniform field at given voltages on electrodes. It is shown that with decreasing needle radius the velocity of the streamer is increased at given voltages on electrodes. This growth continues until a critical radius, after which the growth of the positive streamer velocity practically stops.